The Problem-Based Learning as a Pedagogical Framework for Teaching Master of Public Policy and Master of Public Administration Programs in Latin America - Muñoz-Del Campo, N (SAGE Publications Inc., 2023)
If the aim of developing public policies is to solve social issues, it is worth asking whether the higher education programs for future public servants are being adapted to the demands of our societies. If we also recognize a relationship between education and political capacity, then it is pertinent to study the development of knowledge, skills, and attitudes promoted by these programs and the appropriate teaching-learning strategies employed. Therefore, this study aims to explore the usefulness of one specific active learning method – problem-based learning (PBL) – for teaching public policy in Latin America: Can the PBL be used as a pedagogical framework for Master of Public Policy (MPP) and Master of Public Administration (MPA) programs?. To tackle this debate, I conducted a content analysis (supported on the software ATLAS.ti) from a corpus of information obtained from two axes: First, from a simple of empirical works on PBL I define this tool, identify its main characteristics, and create three categories to examine the implications of the PBL learning framework on the teaching of public policy & administration (PPA) higher education field. Second, through a simple of the region’s MPP and MPA programs, I identify capacities that these programs intend to install in their students. The findings show the implications of the PBL’s learning framework on the teaching of PPA higher education in this field and reveals the usefulness of this tool for achieving the programs’ teaching-learning outcomes. © The Author(s) 2022.